Dynamic Scaling and Growth Kinetics of 3-Glycidoxypropyltrimethoxysilane-Derived Organic/Silica Hybrids - Vollet, Dimas R. [UNESP]; Donatti, Dario A. [UNESP]; Awano, Carlos M. [UNESP]; Chiappim, William [UNESP]; Vicente, Fábio Simões de [UNESP] (Amer Chemical Soc, 2011)
Structural evolution and dynamic scaling properties have been probed by small-angle X-ray scattering (SAXS) in the growth kinetics of 3-glycidoxypropyltrimethoxysilane (GPTS)-derived organic/silica hybrids in basic solution. The SAXS intensity curves were found to be well described by a particle form factor valid for polydisperse coils of linear chains and for particular cases of random and nonrandom polycondensates in solution together with an interference factor accounting for very weak correlations of particles. The SAXS data are consistent with formation and growth of GPTS-derived organic/silica hybrids in solution with polydispersity increasing with time. The following properties have been found: (i) The SAXS intensities I(q,t) corresponding to different times t are given by a time-independent function F(qR(g)) = I(q,t)R(g)(-D), R(g) being the average radius of gyration of the hybrid particles; (ii) the average radius of gyration grows in a power-law with time t as R(g) proportional to t(alpha), with alpha = 0.307 +/- 0.009, suggesting growth of domains by a diffusion-controlled mechanism; (iii) the SAXS intensity I(0) extrapolated to q = 0 increases in a power-law with time t as I(0) proportional to t(beta), with beta = 0.547 +/- 0.020, so beta/alpha = 1.78 +/- 0.12; (iv) the extrapolated intensity I(0) scales with R(g) as I(0) proportional to R(g)(D), with D = 1.69 +/- 0.01, which is in good agreement with the value beta/alpha and suggests that the macromolecules grow in a dimensionality approximate to 1.7, typical of macromolecules in good-solvent conditions in diluted or semidiluted solution. This set of findings is in notable agreement with the dynamic scaling properties. Dynamic scaling properties are important to confront phase-separation theories through the remarkable characteristics of the structure function associated. New insights on the development of the structural heterogeneities in hybrid materials are apprehended from the present dynamics of the sol-gel process probed by SAXS.